The definitions of the base units in the revised SI: A terminological analysis. (January 2020) - Mari, Luca; Goodwin, Joanna; Jacobson, Erik; Pendrill, Leslie
Highlights: A terminological analysis is developed of the unit definitions in the revised SI. Unit definitions in the revised SI are shown to be terminologically problematic. Multiple options are proposed to solve the highlighted problems. Abstract: This paper analyses the structure of the new definitions of the base units in the revised SI and discusses the possible strategies of definition which leads to provide information about the SI units that is (α) in conformity with the 2018 CGPM Resolution 1, (β) terminologically correct, and (γ) as understandable as possible to standards writers and users, translators, textbook writers, and the general public.